Creative corbel modeling using evolution principle - Zhang, Yuzhe (2021)
Corbel is a common category of decorative architectural geometry that has clear structure and aesthetic design. This paper presents a method for automatically generating a group of new corbel models from one selected by the user in the dataset. The method consists of offline learning and online generation. The offline learning trains two VAE models (2D CurveVAE and 3D VoxelVAE) for learning the feature representation of corbel parts. The online generation includes a generation algorithm by evolution that evolves to product new generation of models by crossing over and mutating features, and a feature-driven deformation that synthesizes 3D mesh representation of corbel models. By integrating these technical components, we develop a creative corbel modeling tool capable of generating new corbel models that are both “more of the same” and “surprising”, which is demonstrated by experiments.